KUALITAS SEMEN SEGAR DAN SEMEN CAIR BABI LANDRACE ASAL NAIONI KABUPATEN KUPANG DENGAN SISTEM PEMELIHARAAN INTENSIF - Foeh, Nancy; Gaina, Cynthia; Tophianong, Tarsisius (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2022)
The aims of this study is to determine the quality of fresh cement of Landrace pigs diluted with natural diluent of green coconut water. The research was conducted at the Veterinary Reproduction Laboratory of FKKH Undana. Fresh semen of Landrace pigs was collected from male pigs that less than 3 years sexually mature and in healthy condition, then the semen quality was examined by macroscopic and microscopic evaluation. Only cement met the requirements, the proportion of spermatozoa motility not less than 70%, spermatozoa concentration not less than 200 million cells/ml and spermatozoa abnormality not more than 20%. After that, the semen was diluted by adding green coconut water and antibiotics according to the dilution formula. The results showed that semen diluted with natural green coconut was better and could be used as an alternative diluent with a higher of spermatozoa viability and motility (48.2% & 41.25%) compared to fresh semen with a shelf life of 20 hours.